2004
DOI: 10.1103/physrevb.69.214301
|View full text |Cite
|
Sign up to set email alerts
|

Spectral response of crystalline acetanilide andN-methylacetamide: Vibrational self-trapping in hydrogen-bonded crystals

Abstract: Femtosecond pump-probe and Fourier transform infrared spectroscopy is applied to compare the spectral response of the amide I band and the NH-stretching band of acetanilide (ACN) and N-methylacetamide (NMA), as well as their deuterated derivatives. Both molecules form hydrogen-bonded molecular crystals that are regarded to be model systems for polypeptides and proteins. The amide I bands of both ACN and NMA show a temperature-dependent sideband, while the NH bands are accompanied by a sequence of equidistantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
42
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 51 publications
7
42
0
Order By: Relevance
“…Difference between the vibration intensity of (R,S)-atenolol spectra at −170 • C before and after deuteration in the C-H stretch vibration region. Likewise, N-methylacetamide presents non-fundamental vibration bands at 2900-2650 cm −1 interpreted as Fermi resonances with the overtone and combination modes of amide bands [15].…”
Section: Infrared Spectra Of S-and (Rs)-atenolol In Solid Statementioning
confidence: 99%
“…Difference between the vibration intensity of (R,S)-atenolol spectra at −170 • C before and after deuteration in the C-H stretch vibration region. Likewise, N-methylacetamide presents non-fundamental vibration bands at 2900-2650 cm −1 interpreted as Fermi resonances with the overtone and combination modes of amide bands [15].…”
Section: Infrared Spectra Of S-and (Rs)-atenolol In Solid Statementioning
confidence: 99%
“…The nonlinear pump-probe response of these infrared (IR) transitions, in turn, often decays on an ultrafast (a few 100 fs) time scale [13][14][15] and in some cases also exhibits complex oscillatory features. [6][7][8][9][10][11][12] It is the very anharmonic nature of the hydrogen bond potentials that gives rise to the peculiar vibrational spectroscopy, [16][17][18][19][20][21][22] i.e., in essence the fact that the typical dissociation energy of a hydrogen bond is in the same range as the frequency of its vibrational modes. It has also been shown that the problem is inherently high-dimensional, [17][18][19][20][21][22] which renders the modeling of the quantum dynamics demanding and the interpretation of the computational results complicated.…”
Section: Introductionmentioning
confidence: 99%
“…The prototype example is the OH-stretch vibration of liquid water, where both broadening and solvation shift are a few 100 cm −1 , as opposed to typically 10 cm −1 of "normal" vibrational modes. Furthermore, if a hydrogen bond is of intramolecular nature, [6][7][8] binding a dimer with reasonably well defined structure, 9,10 or in hydrogen-bonded molecular crystals, 11,12 the vibrational band often contains a pronounced substructure. The nonlinear pump-probe response of these infrared (IR) transitions, in turn, often decays on an ultrafast (a few 100 fs) time scale [13][14][15] and in some cases also exhibits complex oscillatory features.…”
Section: Introductionmentioning
confidence: 99%
“…The observation of transitions, spectroscopic frequency shifts or relaxation times of spectral elements were connected to spatial localization by theoretical or numerical analysis not by direct observation as with macroscopic systems. The atomic systems included the analysis of resonant Raman spectra in the highly nonlinear halide-bridged mixed-valence transition metal complex [Pt(en) 2 ][Pt(en) 2 Cl 2 ](ClO 4 ) 4 [47], the anomalous optic mode found with neutron scattering in the monatomic bcc crystal of 4 He [48], the localized 1-D mode identified in alpha uranium [49], and the spectral anomalies interpreted as a signature of vibrational self trapping in hydrogen-bonded acetanilide [50,51]. The temperature dependence of the resonances in KI:Ag + , a theme in this paper, is another thermal equilibrium example.…”
Section: Two Elastic Configurations In Ki:ag + Without Ilmsmentioning
confidence: 99%